Pengaruh Rotasi Audit, Spesialisasi Industri KAP, dan Client Importance Terhadap Kualitas Audit (Studi dengan Pendekatan Earning Surprise Benchmark) - Maya Febrianti Suciana; Mia Angelina Setiawan (Wahana Riset Akuntansi, 2018)
This research was aimed to examine empirically the effect of several factors to audit quality. These factors are Audit Rotation, Audit Firm Specialization and Client Importance. The population that will be used in this research are company listed in Indonesia Stock Exchange. This study uses sampel of 85 manufacturing companies listed in Indonesia Stock Exchange in the period 2015-2017. In this study, audit quality is measured by earning surprise benchmark. The method used was purposive sampling. The method of data analysis in this study use logistic regression with SPPS version 23. The results of this prove that (1) audit rotation is not proven to have an impact on audit quality, where sig value 0,915 > ???? 0,05 which means H1 is rejected (2) audit firm specialization is proven to have an impact on audit quality, where sig value 0,04 < ???? 0,05 which means H2 is accepted (3) client importance is not proven to have an impact on audit quality, where sig value 0,809 > ???? 0,05 which means H3 is rejected. The amount of Adjusted R is 0.036 gives the sense that rate is 3,6% of level audit quality can be explained by independent variables while 96.4% can be explained by the other independent variabels that are not tested in this study.Keywords: Audit Rotation, Audit Firm Specialization, Client Importance, Audit Quality